Klasifikace českých regionů podle trendu vývoje - Kovárník, Jaroslav (Univerzita Pardubice, 2006)
In this article I am concerned with an analysis of in Czech Republic. In the opening chapter, strategy of regional development of Czech Republic is briefly dealt with, later I concentrate on regions in Czech Republic at all. I make short analysis of districts in Czech Republic and I propose to position of regional policy on these districts.
Keywords: regiony; Česká Republika; Regionální politika; regionální diferenciace; rozdíly